Upregulated Expression of Cytotoxicity-Related Genes in IFN-γ Knockout Mice with Schistosoma japonicum Infection. (1st October 2011) - Du, Xiaotang; Wu, Jingjiao; Zhang, Meijuan; Gao, Yanan; Zhang, Donghui; Hou, Min; Ji, Minjun; Wu, Guanling
Abstract : It is well accepted that IFN- γ is important to the development of acquired resistance against murine schistosomiasis. However, the in vivo role of this immunoregulatory cytokine in helminth infection needs to be further investigated. In this study, parasite burden and host immune response were observed in IFN- γ knockout mice (IFNg KO) infected with Schistosoma japonicum for 6 weeks. The results suggested that deficiency in IFN- γ led to decreased egg burden in mice, with low schistosome-specific IgG antibody response and enhanced activation of T cells during acute infection. Microarray and qRT-PCR data analyses showed significant upregulation of some cytotoxicity-related genes, including those from the granzyme family, tumor necrosis factor, Fas Ligand, and chemokines, in the spleen cells of IFNg KO mice. Furthermore, CD8 + cells instead of NK cells of IFNg KO mice exhibited increased transcription of cytotoxic genes compared with WT mice. Additionally, Schistosoma japonicum -specific egg antigen immunization also could activate CD8 + T cells to upregulate the expression of cytotoxic genes in IFNg KO mice. Our data suggest that IFN- γ is not always a positive regulator of immune responses. In certain situations, the disruption of IFN- γ signaling may up-regulate the cytotoxic T-cell-mediated immune responses to the parasite.